Prevalence of circulating tumor cells after adjuvant chemotherapy with or without anthracyclines in patients with HER2-negative, hormone receptor-positive early breast cancer - De Gregorio, Amelie; Schneeweiss, Andreas (Clinical breast cancer, 2017)
Background: Use of anthracycline-based chemotherapy in patients with early breast cancer (EBC) has been well-established but is often associated with cardiotoxicity. Based on data suggesting a limited benefit of anthracyclines in human epidermal growth factor receptor 2 (HER2)-negative patients, the Simultaneous Study of Docetaxel Based Anthracycline Free Adjuvant Treatment Evaluation, as well as Life Style Intervention Strategies (SUCCESS) C study randomized patients to either anthracycline-containing or anthracycline-free chemotherapy. Given the proven prognostic value of circulating tumor cells (CTCs) in EBC, we compared the prevalence of CTCs after chemotherapy between both treatment arms for a preliminary efficacy assessment. Methods: The SUCCESS C trial (NCT00847444) is an open-label, phase III study randomizing 3547 patients with HER2-negative EBC to either 3 cycles of epirubicin, 5-fluorouracil, and cyclophosphamide followed by 3 cycles of docetaxel (FEC-DOC) or 6 cycles of docetaxel and cyclophosphamide (DOC-C). CTC status was prospectively evaluated in hormone receptor-positive patients at the time of last chemotherapy cycle using the US Food and Drug Administration-approved CellSearch System (Janssen Diagnostics). Results: Data on CTC status were available for 1766 patients. Overall, CTCs were found in 221 (12.5%) patients. Univariate analyses revealed that presence of CTCs at time of last chemotherapy cycle was not significantly associated with tumor or patient characteristics (all P > .1). There was no significant difference with respect to presence of CTCs between patients randomized to FEC-DOC or DOC-C (11.5% vs. 13.6%; P = .18). Conclusions: The comparable prevalence of CTCs at the time of last chemotherapy cycle may indicate that anthracycline-free chemotherapy is equally effective to anthracycline-containing chemotherapy in HER2-negative, hormone receptor-positive EBC. However, efficacy data from the final survival analysis of SUCCESS C have to be awaited to confirm these preliminary findings.
Gesehen am 20.08.2018